Berberine Inhibits the Adhesion of Candida albicans to Vaginal Epithelial Cells - Zhao, Ting; Zhang, Kang; Shi, Gaoxiang; Ma, Kelong; Wang, Benfan; Shao, Jing; Wang, Tianming; Wang, Changzhong (Frontiers in Pharmacology, 2022)
Vulvovaginal candidiasis (VVC) is an inflammatory disease of the vagina mainly caused by Candida albicans (C. albicans), which affects around three-quarters of all women during their reproductive age. Although some antifungal drugs such as azoles have been applied clinically for many years, their therapeutic value is very limited due to the emergence of drug-resistant strains. Previous studies have shown that the adhesion of C. albicans to vaginal epithelial cells is essential for the pathogenesis of VVC. Therefore, preventing the adhesion of C. albicans to vaginal epithelial cells may be one of the most effective strategies for the treatment of VVC. Berberine (BBR) is a biologically active herbal alkaloid that was used to treat VVC. However, so far, its mechanism has remained unclear. This study shows BBR significantly inhibits the adhesion of C. albicans to vaginal epithelial cells by reducing the expressions of ICAM-1, mucin1, and mucin4 in vaginal epithelial cells, which play the most important role in modulating the adhesion of C. albicans to host cells, and balancing IL-2 and IL-4 expressions, which play a key effect on regulating the inflammatory response caused by C. albicans infection. Hence, our findings demonstrate that BBR may be a potential therapeutic agent for VVC by interfering with the adhesion of C. albicans to vaginal epithelial cells and represents a new pathway for developing antifungal therapies agents from natural herbs.